The Leadership’s Influence on Staff Performance Through Job Satisfaction at the University of West Sulawesi in Majene Regency - Andi Suryani Syamsuddin; Abdul Rahman Kadir; Syamsu Alam; Madris Madris (AIBPM Publisher, 2022)
Leadership is a leader’s ability to influence an individual or community to reach an aim together. Leadership is a style, an act, or an attitude of a leader to its members. This study aims to analyze the leadership’s influence on job satisfaction and performance achievement at the University of West Sulawesi. This was conducted from October to November 2021 at the University of West Sulawesi. There were 60 participants involving 20 leaders, 20 staff, and 20 students. The participants were taken randomly or it is called random sampling technique with cluster technique. The data in this study was primary data and it was taken through participants’ responses to a questionnaire. The data were analyzed quantitatively with the inferential statistics method. The analysis technique used is Structural Equation Modeling (SEM) with a variance-based approach or component-based approach through Partial Least Square. The result of the study shows that leadership influences significantly on job satisfaction and performance achievement at the University of West Sulawesi. Moreover, job satisfaction also influences significantly on job satisfaction. Keywords: Job Satisfaction, Leadership, Performance, University of West Sulawesi